2016
DOI: 10.1021/acscatal.6b00120
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Asymmetric Catalysis by N-Heterocyclic Carbenes and Brønsted Acid in γ-Lactam Formation: Insights into Mechanism and Stereoselectivity

Abstract: Current developments in the burgeoning area of cooperative asymmetric catalysis indicate the use of N-heterocyclic carbenes (NHCs) in conjunction with other catalysts such as a Brønsted acid. Herein, mechanistic insights derived through a comprehensive DFT (M06-2X) computational study on a dual catalytic reaction between an enal and an imine leading to trans-γ-lactams, catalyzed by a chiral NHC and benzoic acid, is presented. In the most preferred pathway, we note that the NHC catalyst activates one of the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 80 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…This can be attributed to the presence of additional stabilizing non- covalenti nteractions compared to the other conformations, as seen by comparing the corresponding NCI plots [57,93,94] in Figure 3b and through ac omparative AIM analysis (Figure 3c). [90,[95][96][97][98] More precisely,t he NCI plots show greater density of favorable non-covalent interactions (green patches) for Trans(re) comparedt oi ts counterpart. This is corroborated by the stronger (a, b, e, f, g, j) and additional (c, d) non-covalent contacts, successfully captured by AIM analysis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This can be attributed to the presence of additional stabilizing non- covalenti nteractions compared to the other conformations, as seen by comparing the corresponding NCI plots [57,93,94] in Figure 3b and through ac omparative AIM analysis (Figure 3c). [90,[95][96][97][98] More precisely,t he NCI plots show greater density of favorable non-covalent interactions (green patches) for Trans(re) comparedt oi ts counterpart. This is corroborated by the stronger (a, b, e, f, g, j) and additional (c, d) non-covalent contacts, successfully captured by AIM analysis.…”
Section: Resultsmentioning
confidence: 98%
“…An extensive conformational search for both atropisomers of alcohol 1 revealed that the Trans( re) orientation is strongly favored. This can be attributed to the presence of additional stabilizing non‐covalent interactions compared to the other conformations, as seen by comparing the corresponding NCI plots in Figure b and through a comparative AIM analysis (Figure c) . More precisely, the NCI plots show greater density of favorable non‐covalent interactions (green patches) for Trans( re) compared to its counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…Based on Rovis's experimental report, Sunoj and co‐workers investigated the NHC and Brønsted acid cooperatively catalyzed [3+2] annulation reaction between enal 28 and imine 29 for the formation of γ‐lactam 30 at the SMD MeCN ‐M06‐2X/6‐31G(d, p) level in 2016 . As depicted in Scheme , the catalytic cycle begins with the nucleophilic addition of the chiral NHC to the electrophilic enal 28 , leading to the zwitterionic intermediate M49 .…”
Section: Nhc‐catalyzed [3+2] and [4+2] Annulation Reactions Of Carbonmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] More recently, the Sunoj [26][27][28] group performed a theoretical study on mechanisms and enantioselectivity of NHC-catalyzed Stetter and annulation reactions of enals. Moreover, some teams [29][30][31] studied a series of reactions involving the proton transfer process and showed an interesting result that the in situ formed acid can be assisted, which has attracted our attention.…”
mentioning
confidence: 99%